State of the Profession: The Landscape of Disability Justice, Health Inequities, and Access for Patients With Disabilities. (July 2019) - Engelman, Alina; Valderama-Wallace, Claire; Nouredini, Sahar
Abstract : The nursing profession can both perpetuate inequities and elevate the discourse around disability. Our article uses an intersectional lens to discuss the scope, magnitude, and determinants of health inequities that people with disabilities experience and the ways in which theoretical models of disability used in nursing education can further contribute to inequities. Our article makes the case for an intersectional social justice approach to nursing education by contextualizing the current state of affairs within historical and contemporary models of disability. This has the potential to be a revolutionary leap toward promoting health equity and upholding the Code of Ethics .